Proctitis distal to colorectal anastomosis: a retrospective cohort study of an underreported complication after sigmoidectomy - Ajmal Khan; Maziar Nikberg; Kenneth Smedh; Abbas Chabok (Annals of Coloproctology)
Purpose Proctitis distal to colorectal anastomosis is rare and infrequently reported. We evaluated the incidence, symptoms, treatment, and potential risk factors associated with this condition. Methods We conducted a retrospective population-based cohort study in Västmanland County, Sweden. This investigation included all patients who underwent sigmoidectomy with colorectal anastomosis between 2008 and 2020. We excluded patients without an anastomosis and those with inflammatory bowel disease. Results Of the 546 patients identified, 233 fulfilled the inclusion criteria, of whom 26 (11.2%) developed proctitis distal to colorectal anastomosis. The most frequent symptoms included urgency (n=16, 61.5%), increased stool frequency (n=12, 46.2%), and anorectal pain (n=12, 46.2%). Endoscopic balloon dilation was performed in 20 cases (76.9%), with 10 requiring only a single therapeutic procedure. The median number of dilations was 3 (range, 1–8). Multivariable analysis revealed that surgery due to malignancy and emergency surgery were associated with elevated risk of proctitis. A subgroup analysis of patients who underwent surgery due to malignancy indicated that smoking (odds ratio, 3.9; 95% confidence interval, 1.1–14.0) and emergency surgery (odds ratio, 6.5; 95% confidence interval, 1.1–37.1) were also associated with increased proctitis risk. Conclusion Proctitis distal to colorectal anastomosis is not uncommon following sigmoidectomy. Patients undergoing emergency surgery or surgery due to malignancy and who had a history of smoking displayed an increased risk of developing proctitis. Due to the paucity of symptoms observed, particularly in patients with a diverting stoma, routine endoscopic rectal examination should be performed during follow-up after sigmoidectomy.